Questions
1. multiply and simplify if possible.
sq root 6x(sq root x - 2 sq root 6)
2. simplify the expression
2^3 sq root 2x - 4^3 sq root 2x
3. simplify the expression
5^1/2 * 5^1/2
4. rewrite ^3 sq root x^n with a fractional exponent
5. divide and simplify if possible.
sq root(162x^14)/sq root 2x^2
6. find the solution
sq root -x - 5 + 3 = x
7. find the solution
^3 sq root (x + 1)^2 + 5 = 69Questions
1. multiply and simplify if possible.
sq root 6x(sq root x - 2 sq root 6)
2. simplify the expression
2^3 sq root 2x - 4^3 sq root 2x
3. simplify the expression
5^1/2 * 5^1/2
4. rewrite ^3 sq root x^n with a fractional exponent
5. divide and simplify if possible.
sq root(162x^14)/sq root 2x^2
6. find the solution
sq root -x - 5 + 3 = x
7. find the solution
^3 sq root (x + 1)^2 + 5 = 69
please show work for each questions
1 answer
2. 2^3√2x - 4^3√2x = 8√2x - 64√2x = -56√2x
3. 5^1/2 * 5^1/2 = 5^(1/2 + 1/2) = 5^1 = 5
4. ^3√x^n = x^(n/3)
5. √(162x^14)/√(2x^2) = √(162x^14/2x^2) = √81x^12 = 9x^6
6. √-x - 5 + 3 = x
√-x = x + 2
-x = x^2 + 4x + 4
x^2 + 4x + 4 + x = 0
x^2 + 5x + 4 = 0
(x + 1)(x + 4) = 0
x = -1 or x = -4
7. ^3√(x + 1)^2 + 5 = 69
^3√(x + 1)^2 = 64
(x + 1)^2 = 64^3
(x + 1)^2 = 262144
x + 1 = ±√262144 = ±512
x = -1 ± 512
x = 511 or x = -513